The qualitative research interview - DiCicco-Bloom, Barbara; Crabtree, Benjamin F (Medical education, 2006)
Background  Interviews are among the most familiar strategies for collecting qualitative data. The different qualitative interviewing strategies in common use emerged from diverse disciplinary perspectives resulting in a wide variation among interviewing approaches. Unlike the highly structured survey interviews and questionnaires used in epidemiology and most health services research, we examine less structured interview strategies in which the person interviewed is more a participant in meaning making than a conduit from which information is retrieved. Purpose  In this article we briefly review the more common qualitative interview methods and then focus on the widely used individual face‐to‐face in‐depth interview, which seeks to foster learning about individual experiences and perspectives on a given set of issues. We discuss methods for conducting in‐depth interviews and consider relevant ethical issues with particular regard to the rights and protection of the participants.